The Relationship Between Patient Nutritional Status and Mortality Rates in The Intensive Care Unit - Nugroho Ari Wibowo; Arif Zahid Sugiarto; Diah Priyantini; Aries Chandra Ananditha (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: Mortality among ICU patients remains high and is influenced by multiple factors, including nutritional status. Malnutrition may worsen clinical outcomes and increase the risk of death. This study aimed to examine the relationship between nutritional status and mortality in ICU patients. Method: A retrospective correlational study was conducted among adult patients (≥18 years) admitted to the ICU of a hospital in Surabaya between May and December 2023. A total of 185 patients were selected using a total sampling technique. Nutritional status was assessed using Malnutrition Universal Screening Tool (MUST) scores and disease severity was measured using APACHE II. Mortality outcomes were determined based on patient status at ICU discharge and categorized into predefined mortality risk levels. Data were analyzed using the Spearman rank correlation test. Results: Increasing age was significantly associated with higher mortality, with patients aged >65 years showing the highest proportion of high mortality (55.2%; r = 0.62; p < 0.001). Gender was also significantly associated with mortality (r = 0.21; p = 0.041), with males demonstrating a higher proportion of high mortality than females (40.4% vs 29.6%). Nutritional status showed a moderate positive correlation with mortality (r = 0.55; p < 0.001), with higher malnutrition risk associated with increased mortality. Conclusion: Nutritional status is significantly associated with mortality among ICU patients. Early nutritional assessment and appropriate management are essential to improve clinical outcomes and support evidence-based critical care practice.